2018
DOI: 10.1016/j.jad.2017.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition of magnetic resonance imaging-based gray matter volume measurements classifies bipolar disorder and major depressive disorder

Abstract: Our results add to previously published data which suggest that regional gray matter volume should be investigated further as a clinical diagnostic tool to predict BD before the appearance of a manic or hypomanic episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 76 publications
2
39
0
Order By: Relevance
“…Regarding the interest of combining the features, Jie et al 65 also reported higher ACC when integrating multimodal features (ie, 92.07%) in comparison with single modality (90.89% for functional connectivity and 77.83% for grey matter volumes solely). Notably, the ACC of the 3 studies including more than 100 subjects 44,50,67 was below the median ACC of this category (86%).…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…Regarding the interest of combining the features, Jie et al 65 also reported higher ACC when integrating multimodal features (ie, 92.07%) in comparison with single modality (90.89% for functional connectivity and 77.83% for grey matter volumes solely). Notably, the ACC of the 3 studies including more than 100 subjects 44,50,67 was below the median ACC of this category (86%).…”
Section: Literature Reviewmentioning
confidence: 90%
“…Reported ACC for discriminating BD vs MDD ranged between 49.5% and 93.1% (Figure 4). Six studies used only sMRI as input features, 44,48,50,54,66,67 5 studies used grey matter input features reaching 59.45%‐75.9% ACC 44,48,50,66,67 and 1 used both grey and white matter input features reaching 54.76% ACC 54 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Almost all of the selected studies used SVM or its variant method as the primary classification method 22,[40][41][42][44][45][46][47][48][49][50]52,53,82,84,87,[89][90][91]98 and use LOOCV for cross validation. The reason why SVM is the most popular choice among depression classification is because of its useful strengths on including a reliable theoretical foundation and its flexible response to high-dimensional data.…”
Section: Classification Methods and Cross-validationmentioning
confidence: 99%
“…Small studies may also yield a wide range of classification performances and inconsistencies in regions, which contribute to the overall classification [25][26][27]. Previous ML structural MRI studies in BD have typically included <50 BD participants recruited in a single site [23,[28][29][30][31][32][33][34]. The largest currently available neurostructural ML studies investigated 128-190 BD and 127-284 control participants [35][36][37], from up to two sites [22,23,38].…”
Section: Introductionmentioning
confidence: 99%